Christianity in Bakhtin : God and the exiled author - Coates, Ruth (Cambridge studies in Russian literature., 1998)
The work of the great Russian theorist Mikhail Bakhtin has been examined from a wide variety of literary and theoretical perspectives. None of the many studies of Bakhtin begins to do justice, however, to the Christian dimension of his work. Christianity in Bakhtin for the first time fills this important gap. Having established the strong presence of a Christian framework in his early philosophical essays, Ruth Coates explores the way in which Christian motifs, though suppressed, continue to find expression in the work of Bakhtin's period of exile, and re-emerge in texts written during the time of his rehabilitation. Particular attention is paid to the themes of Creation, Fall, Incarnation and Christian love operating within metaphors of silence and exile, concepts which inform Bakhtin's world view as profoundly as they influence his biography.